The regime of Demetrius of Phalerum in Athens, 317-307 BCE : a philosopher in politics - O'Sullivan, Lara. (Mnemosyne, Supplements, 2009)
Erudite and urbane, a scion of the Peripatos, Demetrius of Phalerum dominated Athenian political life for a decade (317-307 B.C.E.) with Macedonian support. Viewed by some as the embodiment of the longed-for 'philosopher-king', Demetrius has been seen a test case for the interplay of philosophical training and political praxis in antiquity. This book, through a close re-examination of the fragmentary and diffuse testimonia for Demetrius' decade, argues that such a view misunderstands his legislative, constitutional and financial reforms, which should rather be seen within the context of Macedonian suzerainty, Athenian self-interest, and contemporary social changes. Such a context also affords a better understanding of the dynamic relations between the Macedonian generals and the preeminent Greek city at the dawn of the Hellenistic era.